Hydrogel-based nanoparticles: revolutionizing brain tumor treatment and paving the way for future innovations - Alireza Shadab; Simin Farokhi; Arshia Fakouri; Neda Mohagheghzadeh; Ali Noroozi; Zahra Sadat Razavi; Arian Karimi Rouzbahani; Hamidreza Zalpoor; Mohamad Mahjoor (European Journal of Medical Research)
Abstract Brain tumor treatment remains a significant challenge due to their high mortality and resistance to current therapies. This paper discusses the promising potential of hydrogel-based nanoparticles as innovative drug delivery systems for brain tumor therapy. Extensive characterization techniques reveal the ability of these Nano-systems to demonstrate prolonged blood circulation and targeted delivery, leading to improved survival rates. Designed with optimized physicochemical characteristics, these nanoparticles effectively cross the blood–brain barrier, circumventing a major impediment to drug delivery to the brain. By delivering drugs directly to the tumor bed, these nanoparticles enhance therapeutic outcomes and minimize adverse effects. In addition, this review investigates the techniques for characterizing, visualizing, and modifying these nanoparticles, as well as the standing challenges and promising research avenues for their clinical application. Further investigations are encouraged by this review to investigate potential advancements in hydrogel-based nanoparticle therapeutic approaches for brain tumors. This includes investigating tailored hydrogels, hybrid systems, computational modeling, and the integration of gene therapy and immunotherapy techniques. The study also addresses the need for enhanced synthesis techniques, stability, scalability, and cost-cutting measures to overcome obstacles and advance the clinical use of hydrogel-based nanoparticles in treating brain tumors. Graphical abstract